The Influence of Compensation, Work Environment and Job Satisfaction on Employee Performance at PT. Sahesa Permata Tangguh - Purba, Melfrianti Romauli; Laia, Indah Damai Hati; Berutu, Sukma Jelita; Sitepu, Jupianus (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study investigates the influence of compensation, work environment, and job satisfaction on employee performance at PT. Sahesa Permata Tangguh. A quantitative approach with an associative research design was used, employing purposive sampling to select 76 employees as the sample. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that the three independent variables simultaneously have a significant effect on employee performance, accounting for 64.9% of the variability in performance. The study concludes that improving employee performance requires fair compensation, a supportive work environment, and enhanced job satisfaction. These findings are expected to serve as a reference for more effective human resource management in the furniture industry.